Food And Beverage Sector Amid The Challenges Of The Covid-19 Pandemic - Joanna Marie Titular; Adelfa Marie Gemarino; Reizel Ramos; Ada Buena Celeste; Nicole Rose Eslofor (IC-ITECHS, 2022)
This qualitative study examined the status, challenges experienced and coping strategies of the food and beverage businesses in the Municipality of Tigbauan amid the COVID-19 pandemic. Face-to-face interviews was conducted among eight (8) purposively selected local owners and managers of food and beverage businesses operating in the municipality of Tigbauan which are DTI registered and the data gathered were processed using thematic analysis. Results revealed that all of the Food and Beverage businesses interviewed have just re-opened after travel restrictions were eased. However, the researchers discovered that when localized lockdowns were implemented and when indoor dining was disallowed, their income was severely affected due to few customers to the extent that some of these businesses had to temporarily close and let go of some employees to avoid further losses. To keep their business afloat, some of them have initiated some strategies such as transitioning from traditional dine-ins to accepting online transactions and take-outs. They have also partnered with delivery riders to accommodate orders of customers who were afraid to leave home. This simply means that the COVID-19 pandemic has not only brought negative effects to the food and beverage sector but also prompted them to be innovative amidst the globalhealth crisis which eventually opened new business opportunities for their prosperity.